Drug Resistance and the Role of Combination Chemotherapy in Improving Patient Outcomes - Denise A. Yardley (International Journal of Breast Cancer)
Resistance to cancer chemotherapy is a common phenomenon especially in metastatic breast cancer (MBC), a setting in which patients typically have had exposure to multiple lines of prior therapy. The subsequent development of drug resistance can result in rapid disease progression during or shortly after completion of treatment. Moreover, cross-class multidrug resistance limits patient treatment choices, particularly in a setting where treatments options are few. One attempt to minimize the impact of drug resistance has been the concurrent use of two or more chemotherapy agents with unrelated mechanisms of action and differing modes of drug resistance, with the intent of blocking the development of multiple intracellular escape pathways essential for tumor survival. Within the past decade, an array of mechanistically diverse agents has augmented the list of combination regimens that may be both synergistic and efficacious in pretreated MBC. The aim of this paper is to review mechanisms of resistance to common chemotherapy agents and to consider current combination treatment options for heavily pretreated and/or drug-resistant patients with MBC.